2017
DOI: 10.18805/ijare.a-4687
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability, correlation and path coefficient analysis for quantitative traits in chickpea genotypes

Abstract: Fifty three germplasm of chickpea were undertaken to determine relationships among yield and some yield components using direct (variability, heritability, and genetic advance) and indirect selection parameters (correlation and path coefficient analysis). The present investigation was carried out at the Agriculture Research Farm of Institute of Agricultural Sciences, Banaras Hindu University, Varanasi during the rabi season of 2011-12. Significant genetic variations were observed among the genotypes for days t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
4
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 9 publications
(9 reference statements)
4
4
2
Order By: Relevance
“…The inter relationship was positive and significant among the yield contributing traits like, number of secondary branches per plant with pods per plant, whereas, it were negative and significant among the traits like number of secondary branches per plant with test weight and pods per plant with test weight. Similar kind of interrelations was reported by Guler et al, (2001) for number of pods per plant and 100 seed weight and Bhanu et. al., (2017) for number of secondary branches per plant with pods per plant and 100 seed weight.…”
Section: Resultssupporting
confidence: 87%
“…The inter relationship was positive and significant among the yield contributing traits like, number of secondary branches per plant with pods per plant, whereas, it were negative and significant among the traits like number of secondary branches per plant with test weight and pods per plant with test weight. Similar kind of interrelations was reported by Guler et al, (2001) for number of pods per plant and 100 seed weight and Bhanu et. al., (2017) for number of secondary branches per plant with pods per plant and 100 seed weight.…”
Section: Resultssupporting
confidence: 87%
“…Also, other positive and significant correlations were found for days to maturity with plant height, number of pod-bearing branches per plant, number of pods per plant, pod length, number of seeds per pod, 100-seed weight, which shows that early maturing genotypes had a significant contribution to increasing the traits; plant height with the number of pod-bearing branches per plant, the number of pods per plant, the number of seeds per pod, indicating that increasing plant height resulted in more podbearing branches that accommodated more pods per plant and significantly increased the number of seeds per pod; pod length with number of seeds per pod and 100-seed weight revealed that seed weight and the number of seeds increased with increased pod length. These results agreed with those of previous workers [46,47,48,49]. Positive, but non-significant associations were for the number of pod-bearing branches per plant with pod length; the number of pods per plant with pod length which referred information of inherent relation among the pairs of combination.…”
Section: Discussionsupporting
confidence: 92%
“…While traits which showed negative direct effect on plants were plant height, numbers of primary branches per plant, number of pods per plant and pod length exerted direct negative effect on seed yield per plant. Similar findings have been recorded by Bhanu et al, (2016) and Keerthiga et al, (2018).…”
Section: Direct and Indirect Effects Of Yield Attributing Traits On Y...supporting
confidence: 91%